Analisis Forensik Aplikasi Michat Menggunakan Metode Digital Forensics Research Workshop - Fanani, Galih; Riadi, Imam; Yudhana, Anton (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The development of information technology has had various positive and negative effects. The positive impact that information technology canÂ haveÂ is to make it easier for people to communicate with others inÂ theÂ world, and the negative impact is that society is out of control when using its applications. It is an attitude that causes various crimes in the world caused by cyberspaceÂ (cybercrime)Â One of the most widely used instant messaging applications isÂ Michat.Â TheÂ MiChatÂ app causes cybercrime, pornography, online gambling, fraud, cyberbullying and drug trafficking. Evidence research is conducted using one of the frameworks of theÂ digital forensic research workshop.Â In this framework, forensic identification, preservation, collection, investigation, analysis, and presentation phases are designed to find evidence of digital crime. The forensic tools used to collect evidence areÂ mobility forensic express pro,Â aÂ DBÂ browser forÂ SQLite,Â andÂ oxygen forensic detective.Â Results are presented in the form of reports and evidence, and text chat files, contacts, images, audio, video, and web caches are generated. Forensic tools have a 100% success rate in finding evidence. Comparing the functions of the three forensic tools,Â the mobility forensic express proÂ has a processing rate of 66.7%,Â DBÂ browser forÂ SQLiteÂ has 33.3%, andÂ oxygen forensic detectiveÂ hasÂ 83.3%.Â Digital evidence can be used as corroborating evidence in a trial